Polarizing plate
By forming a thin polarizing plate with a hard coating layer and a multi-layer retardation layer on the polarizing film of the organic light emitting display device, the problems of display deterioration and short-wavelength light durability caused by reflection in the prior art are solved, and excellent anti-reflection, folding durability and display quality are achieved.
Patent Information
- Application Number
- CN202080060849.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-23
- Filing Date
- 2020-09-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-09-21
AI Technical Summary
The existing organic light emitting display device has deteriorated visibility and contrast due to metal wiring and electrode reflections, and its life is shortened under short wavelength light exposure. At the same time, the folding quality deteriorates when applied to flexible display, which makes it prone to problems such as cracks.
A thin polarizing plate is employed which includes a hard coating layer and a retardant layer formed on the polarizing film, the hard coating layer has a pencil hardness of 0.5H or more and does not require an additional protective layer, and the retardant layer has a multi-layer structure to provide excellent anti-reflection and durability.
A polarizing plate with excellent anti-reflection performance in all directions is realized, while improving durability and folding durability for short-wavelength light, reducing the thickness of the polarizing plate, and improving the display quality of the display device.
Smart Images

Figure CN114341680B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a polarizing plate, an organic light-emitting display device and a display device. Background Art
[0002] An organic light emitting device (OLED) is a self-luminous display device that emits light by itself, which does not require a separate backlight, so that the thickness can be reduced and is conducive to realizing a flexible display device.
[0003] However, in the organic light emitting display device, there is a problem that due to the reflection of external light by metal wiring and metal electrodes formed on the organic light emitting display panel, visibility and contrast are deteriorated, resulting in poor display quality, and life is reduced when exposed to light in a short wavelength range for a long time. In addition, with the increase in the level of demand for weight reduction and thinning of displays or televisions, etc., there is a continuous need to implement the organic light emitting display device to be lighter and thinner, and quality deterioration such as crack generation depending on folding when applied to a flexible display device is also a problem. Summary of the invention
[0004] Technical issues
[0005] An object of the present application is to provide a thin polarizing plate having excellent antireflection performance in all directions including the side as well as the front and having excellent folding durability and durability against short wavelengths.
[0006] Another object of the present application is to provide an organic light-emitting display device to which a polarizing plate is applied and a display device including the organic light-emitting display device.
[0007] Technical Solution
[0008] Unless otherwise stated, the reference wavelength of optical properties (eg, phase difference or refractive index) as mentioned in this specification is about 550 nm.
[0009] In this specification, the term in-plane retardation is an optical characteristic defined by the following Equation 1, and the term thickness direction retardation is an optical characteristic defined by the following Equation 2.
[0010] [Equation 1]
[0011] R in =d×(n x -n y )
[0012] [Equation 2]
[0013] R th =d×(n z -n y )
[0014] In Equation 1 and Equation 2, R in is the in-plane delay, R th is the thickness direction delay, d is the thickness of the first delay layer or the second delay layer, n x is the refractive index of the first retardation layer or the second retardation layer in the slow axis direction, n y is the refractive index of the first retardation layer or the second retardation layer in the fast axis direction, and n z is the refractive index of the first retardation layer or the second retardation layer in the thickness direction.
[0015] Here, the term layer is a layer whose in-plane retardation or thickness-direction retardation is to be measured, and thus, for example, a layer in an equation for obtaining the in-plane retardation or thickness-direction retardation of the retardation layer is the retardation layer.
[0016] In this specification, the terms vertical, horizontal, orthogonal, parallel and angle values defining angles are substantially vertical, horizontal, orthogonal, parallel and may include values that include errors within approximately ±10 degrees, within ±9 degrees, within ±8 degrees, within ±7 degrees, within ±6 degrees, within ±5 degrees, within ±4 degrees, within ±3 degrees, within ±2 degrees or within ±1 degree.
[0017] The polarizing plate of the present application may include a polarizing film, a hard coating formed on the top of the polarizing film, and a delay layer formed on the bottom of the polarizing film. The delay layer may have a single-layer structure or may be a laminate having a multilayer structure. In this specification, the term bottom means the direction from the polarizing film toward the delay layer, and the top means the opposite direction. In an example, when the polarizing plate of the present application has been applied to an organic light-emitting display device, the bottom may be consistent with the direction from the polarizing plate toward the organic light-emitting display panel to be described below, and the top may be consistent with the direction toward the observer side.
[0018] In one example, the polarizing plate of the present application may be a polarizing plate in which a hard coating layer is directly formed on a polarizing film without interposing an additional layer.
[0019] Generally, when an organic light emitting display device is used, a protective film may be applied thereto to protect the polarizing film so that scratches do not occur on the polarizing film, etc. The protective film may be a glass substrate and / or a polymer film.
[0020] However, in the polarizing plate of the present application, for example, the hard coating layer can be directly formed on the top of the polarizing film without applying another layer such as a protective film, and without inserting other layers. Since the hard coating layer having the characteristics to be described below as described above is directly formed on the top of the polarizing film without inserting other layers, it can reduce the total thickness of the polarizing plate while protecting the polarizing film when handling and / or using the organic light-emitting display device. Therefore, a thin polarizing plate having not only excellent durability against short wavelengths but also excellent folding durability can be provided.
[0021] In the present specification, the hard coating layer may be a layer having a pencil hardness equal to or greater than a certain level. The pencil hardness may be measured using a conventional pencil hardness measuring instrument by pulling a pencil lead on the surface of the hard coating layer at a temperature of about 25° C. and a relative humidity of 50% under a load of 500 g and at an angle of 45 degrees. The pencil hardness may be measured by increasing the hardness of the pencil lead in stages until a defect such as an indentation, a scratch or a crack is confirmed to occur on the surface of the hard coating layer.
[0022] In one example, the pencil hardness of the hard coating of the present application may be about 0.5H or greater, and in another example, the pencil hardness may be about 0.6H or greater, 0.7H or greater, 0.8H or greater, 0.9H or greater, 1H or greater, or 2H or greater, or may be 10H or less, 9H or less, 8H or less, 7H or less, 6H or less, 5H or less, 4H or less, 3H or less, or 2H or less.
[0023] In one example, the thickness of the hard coating layer can be in the range of 1 μm to 10 μm. In another example, the thickness can be 1.5 μm or more, 2.0 μm or more, 2.5 μm or more, 3 μm or more, or can be 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4 μm or less, or 3 μm or less.
[0024] Since a hard coating layer having a pencil hardness within the above range while controlling the thickness as described above and / or formed from a material to be described below is applied thereto, even if the hard coating layer is formed alone on top of the polarizing film without inserting an additional layer, it can protect the polarizing plate from external impacts and / or short-wavelength light, and can also ensure the folding durability of the polarizing plate by reducing the thickness of the polarizing plate, etc.
[0025] As such a material for forming a hard coating, a known material for forming a hard coating on a polarizing plate can be used. The hard coating formed on the polarizing plate generally includes: a hard coating formed on the surface of a protective film attached to one side of the polarizing film, or a hard coating formed on a so-called single-sided polarizing plate on which a protective film is attached to one side of the polarizing film and a hard coating and a pressure-sensitive adhesive layer are sequentially formed on the other side, wherein the material for forming such a hard coating may also be equally applicable to the polarizing plate of the present application. In one example, as a hard coating, a hard coating comprising a polymerizable epoxy compound and / or an oxetane compound may be applied. Such a material may be exemplified as a material of a protective layer material formed on one side of a polarizing film, for example, in Korean Patent Publication No. 2019-0072151, Korean Patent Publication No. 2019-0072168, or Korean Patent Publication No. 2019-0072460, etc.
[0026] The hard coating layer in the prior art as described above is not directly formed on the upper surface of the polarizing film in consideration of, for example, tearing of the polarizing film. That is, the hard coating layer applied to the conventional polarizing plate is formed on the surface of the protective film attached to the polarizing plate, and is not directly formed on the polarizing film; or even if it is directly formed on the polarizing film, it is formed on the bottom of the polarizing film, that is, the surface of the polarizing film facing the display device when the polarizing plate is applied to the display device. However, the inventors have found that by applying a hard coating layer to a polarizing plate having a unique structure described in this specification, a polarizing plate having excellent folding durability and short wavelength durability and other desired physical properties can be provided.
[0027] For example, according to the following equation 4, the reflective color value change of the polarizing plate of the present application can be 10 or less.
[0028] [Equation 4]
[0029] ΔE * ab =[(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2
[0030] In Equation 4, ΔL* can be expressed as L* a -L* i , Δa* can be a* a -a* i , Δb* can be b* a -b* i , and L* a , a* a and b*a The polarizing plate can be placed at a temperature of 25°C with a power of 0.75 W / m 2 Up to 0.85W / m 2 The color coordinates L*, a* and b* before exposure to light with a wavelength of 420nm for 50 hours, and L* i , a* i and b* i The polarizing plate can be set at 25°C with a power of 0.75 W / m 2 Up to 0.85W / m 2 The color coordinates L*, a* and b* after exposure to light with a wavelength of 420 nm for 50 hours.
[0031] L, a and b values may refer to L, a and b of the CIE Lab color space as described below. In this color space, the L value represents brightness, wherein an L value of 0 represents black, and an L value of 100 represents white. In addition, when the a value is negative, the color tends to be green, and when it is positive, the color tends to be red or purple. In addition, when the b value is negative, the color tends to be blue, and when the b value is positive, the color tends to be yellow.
[0032] Each numerical value in the CIE Lab color space can be measured by applying a general method for measuring each coordinate of the color space, for example, after placing a spectrophotometer (KONICAMINOLTA, CM-2600d) with a detector in the form of an integrating sphere at the measurement position, it can be measured according to the manufacturer's manual. Such measurement can be performed under temperature conditions of 20°C to 30°C and humidity conditions of 40% to 50%, but is not limited thereto.
[0033] In another example, according to the above equation 4, the reflectance color value change (ΔE* ab ) may be 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less or 0.2 or less, but is not limited to this.
[0034] The polarizing plate of the present application particularly introduces the above-mentioned hard coating layer on the polarizing film without interposing other layers, thereby being able to provide a polarizing plate having a thin thickness while controlling problems such as reduction in the life of the polarizing plate even when it is exposed to a short wavelength for a long time.
[0035] In one example, the thickness of the polarizing plate of the present application may be 45 μm or less. In another example, the thickness of the polarizing plate may be 44 μm or less, 43 μm or less, 42 μm or less, 41 μm or less, 40 μm or less, 39 μm or less, 38 μm or less, 37 μm or less, 36 μm or less, or 35 μm or less, or may be 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, or 35 μm or more, but is not limited thereto.
[0036] By controlling the thickness of the polarizing plate within the above range, a polarizing plate that does not cause appearance defects such as cracks during folding can be provided, and by applying the polarizing plate to an organic light-emitting display device and a flexible display device including the organic light-emitting display device, a flexible display device with excellent folding durability can be provided.
[0037] The polarizing plate of the present application may further include a delay layer on the bottom of the polarizing film. The delay layer may have a single-layer structure or a multi-layer structure. In the case of a multi-layer structure, the delay layer may include, for example, a first delay layer and / or a second delay layer. In one example, the first delay layer is present on the bottom of the polarizing film, and the second delay layer is present on the bottom of the first delay layer, so that the hard coating layer 500, the polarizing film 100, the first delay layer 201 and the second delay layer 202 may be as shown in FIG. Figure 1 Sequentially laminated.
[0038] In this positional relationship, the optical properties of each delay layer are designed as follows, so that when the polarizing plate is applied to a display device, especially an organic light-emitting display device, a polarizing plate can be provided that has excellent anti-reflection performance and / or color characteristics in all directions including the side and front directions and also has short wavelength durability.
[0039] In this specification, the term retardation layer means an element that is an optically anisotropic layer and can convert incident polarized light by controlling birefringence. In this specification, when describing the x-axis, y-axis and z-axis of the retardation layer, unless otherwise specified, the x-axis means a direction parallel to the in-plane slow axis of the retardation layer, and the y-axis means a direction parallel to the in-plane fast axis of the retardation layer, and the z-axis means a thickness direction of the retardation layer. The x-axis and the y-axis may be orthogonal to each other in the plane.
[0040] In the first retardation layer, the in-plane retardation of the above equation 1 (based on a wavelength of 550 nm) may be in the range of about 100 nm to 150 nm. In another example, the in-plane retardation may be about 110 nm or more, 120 nm or more, 130 nm or more, 131 nm or more, 132 nm or more, 133 nm or more, 134 nm or more, 135 nm or more, 136 nm or more, 137 nm or more, 138 nm or more, 139 nm or more, or 140 nm or more, or may be 149 nm or less, 148 nm or less, 147 nm or less, 146 nm or less, 145 nm or less, 144 nm or less, 143 nm or less, 142 nm or less, or 141 nm or less.
[0041] In such an arrangement of the polarizing plate, the first retardation layer can be arranged so that, for example, the slow axis can form an angle in the range of about 35 to 55 degrees with the absorption axis of the polarizing film. In another example, the angle can be about 15 degrees or more, 20 degrees or more, 25 degrees or more, 30 degrees or more, 35 degrees or more, 40 degrees or more, or 45 degrees or more, or can be 65 degrees or less, 60 degrees or less, 55 degrees or less, 50 degrees or less, or about 45 degrees or less. More preferably, it can be arranged to form an angle in the range of about 40 to 50 degrees, but is not limited thereto.
[0042] In the present application, the first retardation layer may also have a dispersion coefficient less than 1 according to the following Equation 3.
[0043] [Equation 3]
[0044] Dispersion coefficient = R in (450) / R in (550)
[0045] In Equation 3, R in (450) is the in-plane retardation of the first retardation layer based on a wavelength of 450 nm, and R in (550) is the in-plane retardation of the first retardation layer based on a wavelength of 550 nm.
[0046] In the present application, the first retardation layer may also be a QWP (quarter wave plate). In the present specification, the term QWP means a wave plate having a 1 / 4 wavelength phase retardation characteristic, wherein the wave plate is used to change incident polarized light that is linearly polarized light into circularly polarized light. In the present specification, the n-wavelength phase retardation characteristic means a characteristic that can delay incident light by n times the wavelength of the incident light within at least a portion of the wavelength range. Therefore, the 1 / 4 wavelength phase retardation characteristic may mean a characteristic that can delay incident light by 1 / 4 times the wavelength of the incident light within at least a portion of the wavelength range.
[0047] In one example, the thickness of the first delay layer of the present application may be 25 μm or less. In another example, the thickness may be 24 μm or less, 23 μm or less, 22 μm or less, 21 μm or less, 20 μm or less, 19 μm or less, 18 μm or less, 17 μm or less, 16 μm or less, 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4 μm or less, or 3 μm or less, or may be 0.1 μm or less. μm or more, 0.2μm or more, 0.3μm or more, 0.4μm or more, 0.5μm or more, 0.6μm or more, 0.7μm or more, 0.8μm or more, 0.9μm or more, 1.0μm or more, 1.1μm or more, 1.2μm or more, 1.3μm or more, 1.4μm or more, 1.5μm or more, 1.6μm or more, 1.7μm or more, 1.8μm or more or 1.9μm or more, but not limited thereto, as long as it can show the desired phase difference.
[0048] In this way, by applying a first delay layer in which the slow axis of the first delay layer and the absorption axis of the polarizing film are set to be within the above-mentioned range while simultaneously exhibiting in-plane delay within the above-mentioned range, it is possible to exhibit an appropriate level of compensation function according to the wavelength in the visible light region by combining with the second delay layer to be described below, thereby ensuring excellent omnidirectional anti-reflection performance, color characteristics and / or short-wavelength durability.
[0049] The polarizing plate of the present application may include, for example, a second retardation layer on the bottom of the first retardation layer. At this time, the second retardation layer may be in contact with the first retardation layer or other elements (such as a pressure-sensitive adhesive layer, etc.), or a polymer film may be present between the first retardation layer and the second retardation layer.
[0050] In the second retardation layer, the thickness direction retardation of the above equation 2 (based on a wavelength of 550 nm) can be in the range of about 30 nm to 150 nm. In another example, the thickness direction retardation can be about 35 nm or more, 40 nm or more, 45 nm or more, 50 nm or more, 55 nm or more, or 60 nm or more, or can be 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less.
[0051] In one example, the second delay layer can be a layer having substantially no in-plane delay. The in-plane delay of such a second delay layer (based on a wavelength of 550 nm) can be, for example, about 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4 nm or less, 3 nm or less, 2 nm or less, or 1 nm or less, or substantially 0 nm.
[0052] As described above, the second retardation layer has substantially no in-plane retardation, so the arrangement of its slow axis does not significantly affect the performance of the polarizing plate. However, when a slow axis exists in the second retardation layer, the arrangement may be perpendicular or horizontal to the absorption axis of the polarizing layer.
[0053] In one example, the thickness of the second retardation layer of the present application may be 10 μm or less. In another example, the thickness may be 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4 μm or less, 3 μm or less, or 2 μm or less, or may be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, 0.6 μm or more, 0.7 μm or more, 0.8 μm or more, or 0.9 μm or more, but not limited thereto, as long as it can show the desired phase difference.
[0054] The range of the thickness direction retardation and the like of the second retardation layer is controlled as above, and the second retardation layer is combined with the above-mentioned first retardation layer at a predetermined position, so that effects suitable for the purpose of the present application can be achieved.
[0055] As the first retardation layer and the second retardation layer, various types of retardation layers may be used without limitation as long as the above-described characteristics are satisfied.
[0056] Generally, as the delay layer, a polymer film imparted with optical anisotropy by stretching such as uniaxial stretching or biaxial stretching, or a liquid crystal film or liquid crystal polymer film formed by orienting and polymerizing a polymerizable liquid crystal compound (so-called RM (reactive mesogen)) is used, and all such known delay layers can be used as long as the above-mentioned characteristics are satisfied.
[0057] In one example, the first retardation layer and / or the second retardation layer may be a liquid crystal film or a liquid crystal polymer film formed by orienting and polymerizing a polymerizable liquid crystal compound, in which case the first retardation layer and / or the second retardation layer may be referred to as a first liquid crystal retardation layer and / or a second liquid crystal retardation layer. Various polymerizable liquid crystal compounds (so-called RMs (reactive liquid crystal elements)) that can be used to manufacture liquid crystal films or liquid crystal polymer films are known, and methods for manufacturing liquid crystal films or liquid crystal polymer films by applying them are known. As such polymerizable liquid crystal compounds, so-called polymerizable nematic liquid crystal compounds or polymerizable smectic liquid crystal compounds and the like are known. Although it is effective to apply such polymerizable liquid crystal compounds from the viewpoint of the ease of adjusting the dispersion coefficient, other types of liquid crystal compounds may also be applied as long as the requirements of the present application are met.
[0058] The stretched polymer film can be exemplified by, for example, a polyolefin film such as a polyethylene film or a polypropylene film, a cycloolefin polymer film such as a polynorbornene film, an acrylic film, a polyvinyl chloride film, a polyacrylonitrile film, a polysulfone film, a polyacrylate film, a polyvinyl alcohol film, or a cellulose ester-based film such as a TAC (triacetyl cellulose) film, or a polyester film such as a PET (poly (ethylene terephthalate)) film or a PC (polycarbonate) film, or a copolymer film of two or more monomers of the monomers forming the polymer, etc. In one example, as the polymer film, a cycloolefin polymer film or an acrylic film can be used. Here, the cycloolefin polymer can be exemplified by a ring-opening polymer of a cycloolefin such as norbornene or a hydrogenated product thereof, an addition polymer of a cycloolefin, a copolymer of a cycloolefin and another comonomer such as an α-olefin, or a graft polymer modified by an unsaturated carboxylic acid or a derivative thereof, etc. of a polymer or a copolymer, but is not limited thereto.
[0059] The polarizing plate of the present application may include other elements on the top and / or bottom of the polarizing film and the first and second retardation layers. However, the polarizing plate may include only the first and second retardation layers as retardation layers. That is, in addition to the polarizing layer and the first and second retardation layers, the polarizing plate may also include only the so-called isotropic layer.
[0060] The isotropic layer mentioned in this specification is a substantially isotropic layer, and even if the related layer has a certain phase difference, it can also be regarded as an isotropic layer, as long as its phase difference does not damage the optical structure designed for the polarizing plate. In one example, the term isotropic layer mentioned in this application is a layer in which the in-plane delay and the thickness direction delay are both 20nm or less. In another example, the delay can be 19nm or less, 18nm or less, 17nm or less, 16nm or less, 15nm or less, 14nm or less, 13nm or less, 12nm or less, 11nm or less, 10nm or less, 9nm or less, 8nm or less, 7nm or less, 6nm or less, 5nm or less, 4nm or less, 3nm or less, 2nm or less, or 1nm or less, or it can be 0nm. Therefore, on the contrary, a layer in which either the in-plane delay and the thickness direction delay exceeds 20nm can be regarded as a delay layer in this application.
[0061] The polarizing plate of the present application further includes, for example, an isotropic layer, wherein a retardation layer may be sequentially formed on a first surface of the isotropic layer, and a second surface of the isotropic layer may be attached to a polarizing film.
[0062] The isotropic layer may be, for example, a triacetyl cellulose film, a cycloolefin polymer film, a polyethylene terephthalate film, a polycarbonate film, a polyvinyl chloride film, a polyacrylonitrile film, a polysulfone film, a polyacrylate film, or a polyvinyl alcohol film, but is not limited thereto.
[0063] The thickness of the isotropic layer may be, for example, in the range of 5 μm to 35 μm. By controlling the thickness of the isotropic layer as above, folding durability and the like can be ensured in accordance with the thinning of the polarizing plate. In another example, the thickness of the isotropic layer can be 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 11 μm or more, 12 μm or more, 13 μm or more, 14 μm or more, 15 μm or more, 16 μm or more, 17 μm or more, 18 μm or more, or 19 μm or more, or can be 34 μm or less, 33 μm or less, 32 μm or less, 31 μm or less, 30 μm or less, 29 μm or less, 28 μm or less, 27 μm or less, 26 μm or less, 25 μm or less, 24 μm or less, 23 μm or less, 22 μm or less, or 21 μm or less.
[0064] In the polarizing plate of the present application, for example, by controlling the ratio (H / P) of the thickness of the hard coating layer (H) to the thickness of the isotropic layer (P), the ratio (H / T) of the thickness of the hard coating layer (H) to the thickness of the delay layer (T), and / or the ratio (H / S) of the thickness of the hard coating layer (H) to the thickness of the polarizing film (S) within a predetermined range, the desired effect can be further maximized.
[0065] In one example, a ratio (H / P) of a thickness (H) of the hard coating layer to a thickness (P) of the isotropic layer may be in a range of 0.01 to 1.5. In another example, the ratio (H / P) of the thickness (H) of the hard coating layer to the thickness (P) of the isotropic layer may be 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, or 0.14 or more, or may be 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.19 or less, 0.18 or less, 0.17 or less, or 0.16 or less.
[0066] In one example, the ratio (H / T) of the thickness (H) of the hard coating layer to the thickness (T) of the delay layer can be in the range of 0.1 to 5. Here, the thickness of the delay layer can mean the thickness of the single-layer structure when the delay layer has a single-layer structure, and can mean the total thickness of all the thicknesses of each layer when the delay layer is a laminate of two or more layers. In one example, when the delay layer has a two-layer structure of a first delay layer and a second delay layer, the thickness (T) of the delay layer can mean the sum of the thickness (T1) of the first delay layer and the thickness (T2) of the second delay layer. In another example, the ratio (H / T) of the thickness (H) of the hard coating layer to the thickness (T) of the delay layer can be 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more, or can be 4.5 or less, 4.0 or less, 3.5 or less, 3.0 or less, 2.5 or less, 2.0 or less, or 1.5 or less.
[0067] In one example, the ratio (H / S) of the thickness (H) of the hard coating layer to the thickness (S) of the polarizing film may be in the range of 0.01 to 1.5. The ratio (H / S) of the thickness (H) of the hard coating layer to the thickness (S) of the polarizing film may be 0.05 or more, 0.1 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, 0.35 or more, or 0.40 or more, or may be 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0068] By controlling the thickness ratio of the hard coating layer to the other layers within a predetermined range as described above, a polarizing plate having excellent effects such as pencil hardness, short wavelength durability, and / or folding durability can be provided.
[0069] The polarizing plate of the present application may also include a pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer may be included to attach the polarizing plate of the present application to a display device. Therefore, the pressure-sensitive adhesive layer may be formed on the bottom of the delay layer. Therefore, the polarizing plate of the present application may include a hard coat layer, a polarizing film, a delay layer, and a pressure-sensitive adhesive layer in the following order. In one example, the pressure-sensitive adhesive layer in the polarizing plate may be formed only on the bottom of the delay layer. Therefore, in the polarizing plate structure, the pressure-sensitive adhesive layer may not be formed on the top of the hard coat layer. As the pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer used in the known polarizing plate may be applied without particular limitation.
[0070] In the present application, the polarizing film may be, for example, a polyvinyl alcohol polarizing film. In the present specification, the terms polarizing film and polarizing plate refer to objects that are distinguished from each other. The polarizing film refers to a film, sheet or element that exhibits a polarizing function itself, and the polarizing film is a functional element that can extract light vibrating in one direction from incident light vibrating in multiple directions. The polarizing plate means an optical element including other elements as well as the polarizing film. Other elements that can be included in the optical element together with the polarizing film can be exemplified as a polarizing film, a protective film or a delay layer, etc., but are not limited thereto.
[0071] Here, the polarizing film may be an absorption polarizing film or a reflection polarizing film, and there is basically no particular limitation. In the present application, the polarizing film may be, for example, a polyvinyl alcohol polarizing film. The term polyvinyl alcohol polarizing film may refer to, for example, a resin film of a polyvinyl alcohol (hereinafter referred to as polyvinyl alcohol) series containing an anisotropic absorbing material such as iodine or a dichroic dye. Such a film can be manufactured by including an anisotropic absorbing material in a polyvinyl alcohol-based resin film and orienting the mixture by stretching, etc. Here, the polyvinyl alcohol-based resin may include a saponification product of polyvinyl alcohol, polyvinyl formal, polyvinyl acetal or ethylene-vinyl acetate copolymer, etc. The degree of polymerization of the polyvinyl alcohol-based resin may be about 100 to 5,000 or about 1,400 to 4,000, but is not limited thereto.
[0072] The thickness of such a polarizing film is not particularly limited, and it can be formed to an appropriate thickness according to the purpose. The thickness of the polarizing film can be, for example, in the range of 1 μm to 100 μm. In another example, the thickness may be 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 11 μm or more, 12 μm or more, or may be 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 19 μm or less, 18 μm or less, 17 μm or less, 16 μm or less, 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, or 7 μm or less, but is not limited thereto.
[0073] Such a polyvinyl alcohol polarizing film can be manufactured, for example, by subjecting a polyvinyl alcohol-based film to at least a dyeing process, a cross-linking process, and a stretching process. In the dyeing process, the cross-linking process, and the stretching process, corresponding treatment baths of a dyeing bath, a cross-linking bath, and a stretching bath are used, respectively, and these corresponding treatment baths can use treatment liquids according to each process.
[0074] During the dyeing process, the anisotropic absorbing material can be adsorbed on the polyvinyl alcohol-based film and / or oriented on the polyvinyl alcohol-based film. The dyeing process can be carried out together with the stretching process. Dyeing can be carried out by immersing the film in a solution containing anisotropic absorbing material, such as an iodine solution. As an iodine solution, for example, an aqueous solution containing iodine ions by iodine and an iodine compound as a solubilizer can be used. As an iodine compound, for example, potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide or titanium iodide can be used. The concentration of iodine and / or iodide ions in the iodine solution can be adjusted considering the optical properties of the desired polarizing film, and such control methods are known. During the dyeing process, the temperature of the iodine solution is generally about 20°C to 50°C or about 25°C to 40°C, and the immersion time is generally about 10 seconds to 300 seconds or about 20 seconds to 240 seconds, but is not limited thereto.
[0075] The cross-linking process performed during the manufacture of the polarizing film can be performed using, for example, a cross-linking agent such as a boron compound. The order of the cross-linking process is not particularly limited, for example, it can be performed together with the dyeing process and / or the stretching process, or it can be performed alone. The cross-linking process can also be performed several times. As a boron compound, boric acid or borax can be used. Boron compounds can generally be used in the form of an aqueous solution or a mixed solution of water and an organic solvent, and an aqueous solution of boric acid is generally used. The concentration of boric acid in the aqueous solution of boric acid can be selected within an appropriate range in consideration of its degree of cross-linking and heat resistance, etc. Iodine compounds such as potassium iodide can also be included in the aqueous solution of boric acid, etc.
[0076] The cross-linking process can be carried out by immersing the polyvinyl alcohol-based film in an aqueous boric acid solution, etc., and in this process, the treatment temperature is generally in the range of 25°C or higher, 30°C to 85°C or 30°C to 60°C, and the treatment time is generally 5 seconds to 800 seconds or 8 seconds to 500 seconds.
[0077] The stretching process is usually carried out by uniaxial stretching. The stretching can also be carried out together with the dyeing process and / or the crosslinking process. The stretching method is not particularly limited, wherein for example, a wet stretching method can be applied. In such a wet stretching method, for example, stretching is usually carried out after dyeing, but stretching can be carried out together with crosslinking, which can also be carried out multiple times or in multiple stages.
[0078] The treatment liquid applied to the wet stretching method may contain an iodide compound such as potassium iodide. In the stretching, the treatment temperature is generally in the range of about 25°C or higher, 30°C to 85°C or 50°C to 70°C, and the treatment time is generally 10 seconds to 800 seconds or 30 seconds to 500 seconds, but is not limited thereto.
[0079] In the stretching process, the total stretching ratio can be adjusted in consideration of the orientation characteristics, and based on the original length of the polyvinyl alcohol-based film, the total stretching ratio can be 3 to 10 times, 4 to 8 times, or 5 to 7 times, but is not limited thereto. Here, in the case of accompanying stretching even in the swelling process, etc., the total stretching ratio may mean a cumulative stretching ratio including stretching in each process. The total stretching ratio can be adjusted to an appropriate range in consideration of the orientation, processability, or stretching and cutting possibilities of the polarizing film, etc.
[0080] In the manufacturing process of the polarizing film, in addition to dyeing, cross-linking and stretching, a swelling process can be performed before the above processes. The swelling can clean the pollutants or anti-blocking agent on the surface of the polyvinyl alcohol-based film surface, thereby also having the effect of reducing unevenness such as dyeing deviation.
[0081] In the swelling process, water, distilled water or pure water, etc. can be used. The main component of the relevant treatment liquid is water, and if necessary, an iodide compound such as potassium iodide, or an additive such as a surfactant, or alcohol, etc. can be contained in a small amount.
[0082] The treatment temperature during the swelling process is generally about 20° C. to 45° C. or 20° C. to 40° C., but is not limited thereto. Since swelling deviation may lead to dyeing deviation, the process parameters may be adjusted to suppress the occurrence of such swelling deviation as much as possible.
[0083] If necessary, suitable stretching can also be performed during the swelling process. Based on the original length of the polyvinyl alcohol-based film, the stretching ratio can be about 6.5 times or less, 1.2 times to 6.5 times, 2 times to 4 times, or 2 times to 3 times. The stretching during the swelling process can be controlled so that the stretching in the stretching process performed after the swelling process can be controlled to be small, and the stretching during the swelling process can be controlled so that the stretching break of the film does not occur.
[0084] In the manufacturing process of the polarizing film, a metal ion treatment can be performed. Such a treatment is performed, for example, by immersing the polyvinyl alcohol-based film in an aqueous solution containing a metal salt. Thus, metal ions can be included in the polarizer, and in the process, by adjusting the type or ratio of the metal ions, the hue of the polyvinyl alcohol-based polarizing film can be adjusted. Applicable metal ions can be exemplified by transition metals such as metal ions of cobalt, nickel, zinc, chromium, aluminum, copper, manganese or iron, and the hue can also be adjusted by selecting its appropriate type.
[0085] In the manufacturing process of the polarizing film, a washing process may be performed after dyeing, cross-linking and stretching. Such a washing process may be performed with water or a solution of an iodide compound such as potassium iodide.
[0086] Washing with water and washing with an iodide compound solution may also be combined, and a solution containing a liquid alcohol such as methanol, ethanol, isopropanol, butanol, or propanol may also be used.
[0087] After such a process, a drying process may be performed to produce a polarizing film. The drying process may be performed at an appropriate temperature for an appropriate time, for example, in consideration of the moisture content required for the polarizing film, and such conditions are not particularly limited.
[0088] In one example, the polarizing film may include a zinc component such as zinc ions to ensure high temperature durability of the polarizing plate.
[0089] The content of zinc component can be further adjusted. For example, polarizing film can include zinc component (Zn) in the range of 0.1 wt % to 10 wt %. In another example, the content can be about 0.2 wt % or more, 0.3 wt % or more, 0.4 wt % or more, or 0.5 wt % or more, or can be 9 wt % or less, 8 wt % or less, 7 wt % or less, 6 wt % or less, 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.9 wt % or less, 0.8 wt % or less, 0.7 wt % or less, 0.6 wt % or less, 0.5 wt % or less, 0.4 wt % or less, or 0.3 wt % or less.
[0090] By including the zinc component in the polarizing film in such a form, it is possible to provide a polarizing plate having excellent high-temperature durability which can maintain excellent optical characteristics even when held and / or driven at high temperatures.
[0091] The present application also relates to the use of a polarizing plate, which can be effectively applied to, for example, an organic light-emitting display device. Figure 2 FIG. 1 is a cross-sectional view showing an organic light emitting display device by way of example. Figure 2 The organic light emitting display device 60 includes an organic light emitting display panel 600 and a polarizing plate 10 located on one side of the organic light emitting display panel 600. Compared with the polarizing film 100, the first retardation layer 201 and the second retardation layer 202 of the polarizing plate 10 may be disposed adjacent to the organic light emitting display panel 600.
[0092] The organic light emitting display panel may include a base substrate, a lower electrode, an organic light emitting layer, an upper electrode, and a sealing substrate, etc. One of the lower electrode and the upper electrode may be an anode and the other may be a cathode. The anode is an electrode that injects holes, which may be made of a conductive material having a high work function, and the cathode is an electrode that injects electrons, which may be made of a conductive material having a low work function. At least one of the lower electrode and the upper electrode may be made of a transparent conductive material such as ITO or IZO through which the emitted light can be emitted to the outside. The organic light emitting layer may contain an organic material that can emit light when a voltage is applied to the lower electrode and the upper electrode.
[0093] Additional layers may be included between the lower electrode and the organic light-emitting layer and between the upper electrode and the organic light-emitting layer. Additional layers may include a hole transport layer, a hole injection layer, an electron injection layer, and an electron transport layer for balancing electrons and holes, but are not limited thereto. The sealing substrate may be made of glass, metal, and / or a polymer, and may seal the lower electrode, the organic light-emitting layer, and the upper electrode to prevent moisture and / or oxygen from being introduced from the outside.
[0094] The polarizing plate 10 may be disposed on the side from which light is emitted from the organic light-emitting display panel 600. For example, in the case of a bottom emission structure in which light is emitted toward a base substrate, it may be disposed outside the base substrate, and in the case of a top emission structure in which light is emitted toward a sealing substrate, it may be disposed outside the sealing substrate. The polarizing plate 10 may improve the display characteristics of the organic light-emitting device by preventing external light from being reflected by a reflective layer made of metal, such as electrodes and wirings of the organic light-emitting display panel 600, and preventing external light from being emitted from the organic light-emitting device 60. In addition, since the polarizing plate 10 of the present application may exhibit an anti-reflection effect both on the side and on the front, as described above, lateral visibility may be improved.
[0095] The present application also relates to a display device including an organic light-emitting device. In one example, the display device may be a flexible display device. When the organic light-emitting device including the polarizing plate of the present application is applied to a display device, other components constituting the device or methods constituting the device are not particularly limited, and any material or method known in the relevant art may be used as long as the organic light-emitting device is used. When the organic light-emitting device including the polarizing plate of the present application is applied to a flexible display device, a flexible display having excellent omnidirectional anti-reflection performance, folding durability, and short-wavelength durability may be provided.
[0096] Beneficial Effects
[0097] The present application can provide a thin polarizing plate having excellent anti-reflection performance in all directions including the side and front and having excellent folding durability and durability to short wavelengths. In addition, the present application can provide an organic light-emitting display device using a polarizing plate and a display device including the organic light-emitting display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0098] Figure 1 1 is an exemplary diagram showing a polarizing plate of the present application.
[0099] Figure 2 is an exemplary diagram illustrating an organic light emitting display device.
[0100] Figure 3 shows the state after the polarizing plate of Example 1 is subjected to a folding test, and Figure 4 The state after the polarizing plate of Comparative Example 1 was subjected to a folding test is shown.
[0101] Description of Reference Numerals
[0102] 10: Polarizing plate
[0103] 100: Polarizing film
[0104] 201: First delay layer
[0105] 202: Second delay layer
[0106] 500: Hard coating
[0107] 60: Organic light-emitting display device
[0108] 600: Organic light-emitting display panel
[0109] 70: Crack DETAILED DESCRIPTION
[0110] Hereinafter, the contents of the present application will be described in more detail through Examples and Comparative Examples, but the scope of the present application is not limited to the contents set forth below.
[0111] Preparation Example 1
[0112] A poly(vinyl alcohol) film (Kuraray, TS20) having a thickness of about 20 μm was immersed in a dyeing solution at 28°C containing 0.3 wt% iodine (I2) and 3.0 wt% potassium iodide (KI) for 60 seconds and subjected to a dyeing treatment. Subsequently, the dyed polyvinyl alcohol film was immersed in an aqueous solution (cross-linking solution) at 35°C containing 1 wt% boron and 3 wt% potassium iodide (KI) for 60 seconds and subjected to a cross-linking treatment. Then, the cross-linked polyvinyl alcohol film was stretched at a stretching ratio of 5.4 times by using an inter-roll stretching method. The stretched polyvinyl alcohol film was washed by immersing it in ion exchange water at 25°C for 60 seconds and immersed in an aqueous solution at 25°C containing about 3.0 wt% zinc nitrate for 30 seconds. Then, the polyvinyl alcohol film was dried at a temperature of 80°C for 60 seconds to produce a polyvinyl alcohol polarizing film.
[0113] Example 1
[0114] In order to evaluate folding durability and high-temperature durability, a polarizing plate including a laminate including a hard coating layer, a polarizing film, and a retardation layer in sequence was manufactured.
[0115] As the polarizing film, the polarizing film manufactured in Preparation Example 1 was used. The final thickness of the manufactured polarizing film was about 7 μm or so, and the zinc component was contained in an amount of about 0.2 wt % to 0.3 wt %.
[0116] The laminate of the retardation layers was produced as follows.
[0117] First, a substantially isotropic triacetyl cellulose film (about 20 μm thick) was prepared, in which a polymerized layer (first liquid crystal retardation layer) of a polymerizable liquid crystal compound (Fuji) having reverse dispersion characteristics and having an in-plane retardation of about 141 nm for a wavelength of 550 nm and capable of acting as a QWP (quarter wave plate) was formed on one side to a thickness of about 2 μm. On the first liquid crystal retardation layer of the film, a vertical alignment film was coated by a bar coating method, a polymerizable liquid crystal compound (Merck) was coated on the vertical alignment film, and the polymerizable liquid crystal compound was polymerized in a vertical alignment state to form a positive C film (second liquid crystal retardation layer) having a thickness-direction retardation of about 62 nm for a wavelength of 550 nm to a thickness of 1 μm, thereby manufacturing a retardation layer having a multilayer structure.
[0118] Thereafter, a retardation layer having a multilayer structure was attached to one side of the polarizing film using an optical UV adhesive (thickness: 2 μm). At this time, the surface of the triacetylcellulose film on which the first liquid crystal retardation layer and the second liquid crystal retardation layer were not formed was attached to the polarizing film, and the laminate of the retardation layers was arranged so that the smaller angle among the angles formed by the slow axis of the first liquid crystal retardation layer and the absorption axis of the polarizing film was 45 degrees.
[0119] At the same time, on the other side of the polarizing film, a UV adhesive (LG CHEM) having a hard coating function and containing an epoxy compound and an oxetane compound was applied, and the release-treated side of the polyethylene terephthalate film on one side was attached to the applied UV adhesive layer, and then passed through a UV lamp, thereby forming a hard coating layer with a thickness of about 3 μm and a pencil hardness of about 2H. Finally, the polyethylene terephthalate film was peeled off.
[0120] As a result, a polarizing plate having a structure in which hard coating layer / polarizing film / UV adhesive layer / triacetylcellulose film / first liquid crystal retardation layer / second liquid crystal retardation layer were sequentially laminated was manufactured. The final thickness of the polarizing plate was about 35 μm.
[0121] Comparative Example 1
[0122] In order to evaluate folding durability and high-temperature durability, a polarizing plate including a laminate of a cycloolefin film, a polarizing film, a hard coating layer, and a retardation layer in sequence was prepared.
[0123] As the polarizing film, the polarizing film prepared in Preparation Example 1 was used. The final thickness of the manufactured polarizing film was about 7 μm or so, and the zinc component was contained in an amount of about 0.2 wt % to 0.3 wt %.
[0124] A hard-coated cycloolefin polymer film (Zeon, about 29 μm thick) was attached to one side of the polarizing film using an optical UV adhesive (thickness: 2 μm), and a hard coating layer was coated on the other side of the polarizing film by bar coating to a thickness of about 3 μm.
[0125] At the same time, a laminate of the retardation layer is manufactured by coating a QWP (quarter wave plate) liquid crystal (Fuji) having reverse dispersion characteristics and an in-plane retardation of 141 nm at a wavelength of 550 nm to a thickness of about 2 μm on a positive C film (Merck, thickness of about 1 μm) having a thickness direction retardation of 62 nm at a wavelength of 550 nm.
[0126] Thereafter, the liquid crystal layer portion of the laminate of the retardation layers was attached to the hard coating layer using a general optical UV adhesive (thickness: 2 μm).
[0127] As a result, a polarizing plate having a structure in which a laminate of cycloolefin polymer film / UV adhesive layer / polarizing film / hard coat layer / UV adhesive layer / retardation layer was sequentially laminated (reverse dispersion QWP / positive C film) was manufactured and had a final thickness of about 46 μm.
[0128] Evaluation Example 1 Folding durability test
[0129] After the polarizing plates of Examples and Comparative Examples were placed in a folding test chamber (YMRTC, YM-THC 430S), folding durability was evaluated.
[0130] At this time, for the embodiments and comparative examples, the conditions were set as: (1) folding 200,000 times at 25°C / 20%, (2) folding 20,000 times at 60°C / 20%, (3) folding 20,000 times at 60°C / 90%, (4) folding 20,000 times at -20°C / 0%, and for each condition, the durability was tested by folding at a rate of 60 times / minute.
[0131] After the test was completed, the polarizing plate was inspected for appearance defects such as cracks and tears, and the results are shown in Tables 1 and Figure 3 and Figure 4 middle.
[0132] Evaluation Example 2 Evaluation of reflectance color value changes
[0133] The polarizing plates of the embodiment and the comparative example were each attached to an OLED panel (reflectivity of 55% for a wavelength of 550 nm) so that the first retardation layer and the second retardation layer were closer to the OLED panel than the polarizing film. Then, the color coordinates L, a, and b of the polarizing plate were measured before / after the short wavelength test using KONICAMINOLTA's CM-2600d device.
[0134] In this specification, the short wavelength test is a test in which the polarizing plate is placed in a room (Atlas) at a temperature of 25°C and the polarizing plate is exposed to light at 0.75 W / m 2 Up to 0.85W / m 2 The amount of light is tested by exposure to light with a wavelength of 420nm for 50 hours.
[0135] The measured results and the reflectance color value change (ΔE*) calculated according to the following equation 4 ab ) values are shown in Table 2.
[0136] [Table 1]
[0137]
[0138] [Table 2]
[0139]
[0140]
[0141] It can be confirmed that, as shown in Table 1 and Figure 3 As shown in Tables 1 and 2, no cracks occurred in the polarizing plate of Example 1 even after folding 200,000 times at 25°C / 20% (condition (1)). Figure 4 As shown, after the folding test under the same conditions as in Example 1, cracks occurred in the polarizing plate of Comparative Example 1.
[0142] As shown in Table 2 above, the polarizing plate of Example 1 also has a smaller reflectance color value change (ΔE* ab ), which confirms that the polarizing plate of the present application has excellent short-wavelength durability.
Claims
1. A polarizing plate, comprising: polarizing film; forming a hard coating layer on top of the polarizing film; a retardation layer formed on the bottom of the polarizing film; and Isotropic layer, wherein the hard coating layer is formed directly on top of the polarizing film without intervening other layers, wherein the retardation layer is formed on a first surface of the isotropic layer, and a second surface of the isotropic layer is attached to the polarizing film through a UV adhesive layer, wherein the isotropic layer has an in-plane retardation of 20 nm or less and a thickness-direction retardation of 20 nm or less, Wherein the reflectance color value changes ΔE* according to the following equation 4 ab is 10 or less, [Equation 4] ΔE * ab =[(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2 Where ΔL* is L* a -L* i , Δa* is a* a -a* i , Δb* is b* a -b* i , and L* a 、a* a and b* a The polarizing plate was placed at a temperature of 25°C with a power of 0.75 W / m 2 Up to 0.85W / m 2 The color coordinates L*, a* and b* before exposure to light with a wavelength of 420nm for 50 hours, and L* i 、a* i and b* i In order to make the polarizing plate at a temperature of 25°C with a power of 0.75 W / m 2 Up to 0.85W / m 2 The color coordinates L*, a* and b* after exposure to light with a wavelength of 420 nm for 50 hours. 2 . The polarizing plate according to claim 1 , wherein the hard coating layer has a pencil hardness of 0.5H or more. 3 . The polarizing plate according to claim 1 , wherein a thickness of the hard coating layer is in a range of 1 μm to 10 μm. 4 . The polarizing plate according to claim 1 , wherein a thickness of the polarizing plate is 45 μm or less.
5. The polarizing plate according to claim 1, wherein the retardation layer comprises: a first retardation layer, the first retardation layer being located on the bottom of the polarizing film, having an in-plane retardation according to the following equation 1 in a range of 100 nm to 150 nm based on a wavelength of 550 nm, and being arranged so that a smaller angle among angles formed by a slow axis and an absorption axis of the polarizing film forms an angle in a range of 35 degrees to 55 degrees; and a second retardation layer located on the bottom of the first retardation layer and having a thickness direction retardation according to the following Equation 2 in a range of 30 nm to 150 nm based on a wavelength of 550 nm: [Equation 1] R in =d×(n x -n y ) [Equation 2] R th =d×(n z -n y ) Among them, R in is the in-plane delay, R th is the thickness direction delay, d is the thickness of the first delay layer or the second delay layer, n x is the refractive index of the first retardation layer or the second retardation layer in the slow axis direction, n y is the refractive index of the first retardation layer or the second retardation layer in the fast axis direction, and n z is the refractive index of the first retardation layer or the second retardation layer in the thickness direction.
6. The polarizing plate according to claim 5, wherein the dispersion coefficient of the first retardation layer according to the following equation 3 is less than 1, [Equation 3] Dispersion coefficient = R in (450) / R in (550) in, R in (450) is the in-plane retardation of the first retardation layer based on a wavelength of 450 nm, and R in (550) is the in-plane retardation of the first retardation layer based on a wavelength of 550 nm. 7 . The polarizing plate according to claim 1 , wherein a ratio H / S of a thickness H of the hard coating layer to a thickness S of the polarizing film is in a range of 0.01 to 1.
5. 8 . The polarizing plate according to claim 1 , wherein a ratio H / T of a thickness H of the hard coating layer to a thickness T of the retardation layer is in the range of 0.1 to 5. 9 . The polarizing plate according to claim 1 , wherein a ratio H / P of a thickness H of the hard coating layer to a thickness P of the isotropic layer is in a range of 0.01 to 1.
5. 10 . The polarizing plate of claim 1 , further comprising a pressure-sensitive adhesive layer formed only on a bottom of the retardation layer. An organic light emitting display device, comprising the polarizing plate according to claim 1 . 12 . A display device, comprising the organic light emitting display device according to claim 11 .
Citation Information
Patent Citations
Polarizing plate, method for manufacturing polarizing plate, and image display device
CN104364683A
Antireflection optical filter and organic light-emitting device
CN109844581A
Polarizing plate for OLED and optical display apparatus comprising the same
KR1020170117961A